Kegiatan Pengabdian Masyarakat Berupa Pemeriksaan Rutin Asam Urat Pada Kelompok Usia Dewasa di SMA Santo Yoseph, Cakung - Nicholas Albert Tambunan; Alexander Halim Santoso; Steven Hizkia Lucius; Edwin Destra; Farell Christian Gunaidi (Compromise Journal Community Proffesional Service Journal, 2024)
Uric acid is the end product of purine metabolism in the body, generated from the breakdown of purine substances found in certain foods. When uric acid levels in the body exceed normal limits due to excessive production or impaired excretion, uric acid crystals can accumulate in the joints, leading to a condition known as gout. This Community Service initiative aims to enhance understanding among adults regarding the risks of high uric acid levels and preventive efforts through routine screening and health education. The program is structured using the Plan-Do-Check-Act (PDCA) method to provide comprehensive education on risk factors and prevention, as well as to assess participants' uric acid levels. This initiative emphasizes the importance of a healthy lifestyle and routine examinations as preventive measures, supporting early detection and management of health risks related to uric acid. The continuity of this service activity is expected to improve community quality of life over time.